Exposure of ventilation system cleaning workers to harmful microbiological agents - Małgorzata Gołofit-Szymczak; Anna Ławniczek-Wałczyk; Rafał L. Górny (Nofer Institute of Occupational Medicine, 2013)
Background: Regular inspection of the cleanliness of the ventilation systems, as well as their periodic cleaning and disinfection, if necessary, are the main factors of the proper maintenance of each system. Performing maintenance operations on the ventilation system, workers are exposed to risk associated with the exposure to harmful biological agents. The aim of this study was to assess the employees' exposure to bioaerosols during maintenance work on ventilation systems. Material and Methods: Bioaerosol measurements were carried out using a button sampler. The microbial particles were collected on gelatin filters. Settled-dust samples from the inner surface of the air ducts and filter-mat samples were selected for the microbiological analysis. In the collected air, dust and filter samples the concentration of bacteria and fungi were determined. Results: Bacteria and fungi concentrations ranged between 3.6×102-2.2×104 CFU/m3 and 4.7×102-4.5×103 CFU/m3 at workplaces where the operations connected with mechanical ventilation cleaning were performed and 2.2×104-1.2×105 CFU/m3 and 9.8×101-2.5×102 CFU/m3 at workplaces where filter exchange was performed, respectively. The qualitative analysis of microorganisms isolated from the air in all studied workplaces revealed that the most prevalent bacteria belonged to Bacillus genus. The average concentrations of bacteria and fungi in filter-mat samples were 3.3×103 CFU/cm2 and 1.4×104 CFU/cm2, respectively. In settled-dust samples, average concentrations were 591 CFU/100 cm2 and 52 CFU/100 cm2, for bacteria and fungi respectively. Conclusions: Workers cleaning ventilation systems are exposed to harmful biological agents classified into risk groups, 1 and 2, according to their level of the risk of infection. The research conducted in the workplace can be the basis of risk assessment related to exposure to harmful biological agents during maintenance work in ventilation. Med Pr 2013;64(5):613-623